2017
DOI: 10.1186/s12885-017-3375-5
|View full text |Cite
|
Sign up to set email alerts
|

Calretinin as a blood-based biomarker for mesothelioma

Abstract: BackgroundMalignant mesothelioma (MM) is a deadly cancer mainly caused by previous exposure to asbestos. With a latency period up to 50 years the incidence of MM is still increasing, even in countries that banned asbestos. Secondary prevention has been established to provide persons at risk regular health examinations. An earlier detection with tumor markers might improve therapeutic options. Previously, we have developed a new blood-based assay for the protein marker calretinin. Aim of this study was the veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 40 publications
6
55
0
Order By: Relevance
“…Informed written consent was obtained from all donors, and the study was approved by the Local Research Ethics Committee in Dresden (EK74032013). There was no correlation between sCRT and age as confirmed by our own data set ( p = 0.15) and by previous studies . Nevertheless, individuals for blood donation were selected in an age range matching the included ovarian cancer patients, with the majority of donors ranging between 50 and 75 years.…”
Section: Methodssupporting
confidence: 58%
See 4 more Smart Citations
“…Informed written consent was obtained from all donors, and the study was approved by the Local Research Ethics Committee in Dresden (EK74032013). There was no correlation between sCRT and age as confirmed by our own data set ( p = 0.15) and by previous studies . Nevertheless, individuals for blood donation were selected in an age range matching the included ovarian cancer patients, with the majority of donors ranging between 50 and 75 years.…”
Section: Methodssupporting
confidence: 58%
“…sCRT was highly elevated at primary diagnosis of ovarian cancer and accurately discriminated cases from healthy controls (AUC = 0.85), which is comparable to a study on German and Australian mesothelioma patients, reporting on sCRT elevation in patient blood and a discrimination of cases and controls with an AUC of 0.83 and 0.91, respectively. 20 We additionally reported that sCRT allows, albeit with less discriminative power, detection of particularly early disease (FIGO I-II; AUC = 0.67). However, this analysis was based on only 19 patients and does not allow a statistically substantiated conclusion.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations